Species composition of Amphibians and Reptiles from Phu Yen province - Chung, Ngo Dac; Ngoc, Tran Duy (Academia Journal of Biology, 2014)
According to the statistics that we have made in the Phuyen province, there are 21 amphibian species which belonging to 6 families, 2 orders and 50 reptile species which belonging to 14 families, 3 orders in this area. The herptile species composition of the Phuyen province is higher than the ones of the Konplong district and the NgocLinh mountian (Kontum province) and the west area of the Quangnam province. Among these 71 herptile species in the Phuyen province, 31 species are precious, with 16 species listed in the IUCN Red List (2004), 18 species in the Red Data Book of Vietnam (2000), 13 species in the CITES appendices and 15 species in the Governmental Decree No, 48/2002/N§-CP. Six species are endemic of Vietnam.